Marketing/Promotional Initiatives by Pharmaceutical Companies 2013; 201C;Doctor2019;s Perspective201D; (Global Journal of Medical Research, 2020)
The study was aimed to obtain the current perception of the different specialities of doctors about the promotional engagement initiatives established and implemented by the Pharmaceutical firms The objective was to understand the need gaps and doctor s preferences in the area of promotional engagement initiatives by conducting face-to-face interviews Analysis of Sales force Sales Representatives effectiveness was also a part of the project This was an attempt to understand the relationship between the sales representatives and the physicians which weights to influence the prescription generation The preference of the physician towards the traits of a Sales Representative where identified The behavioural and professional characteristics of the representatives were the area of focus This feedback was employed to improve the approach by the representatives towards the Physicians
Keywords: e-detailing; Pharmaceutical promotion